Diamond-iron-based magnetic composite abrasive and preparation method thereof
Patent Information
- Application Number
- CN202510943888.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-09
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-07-09
AI Technical Summary
这3种方法都要经历高温过程,容易导致金刚石与铁基体反应或石墨化,因而很少采用最硬的物质金刚石作磨粒,大多采用氧化铝或碳化硅等硬质陶瓷磨粒
[0023] This invention offers the following advantages: It utilizes readily available and inexpensive iron oxide powder, nickel oxide powder, and diamond abrasive grains as the shell material. Employing a low-temperature pre-reduction + high-temperature reduction sintering process, over 90% of the iron oxide powder and metal oxide powder containing solid solution elements (such as nickel oxide) are first reduced at low temperatures, minimizing oxygen damage to the diamond under high-temperature conditions while maintaining the powder's sintering activity. Then, sintering at a maximum temperature of 800℃ allows the iron and nickel to alloy and densify, improving the shell's strength, hardness, corrosion resistance, and effective bonding with the diamond abrasive grains, while preventing significant graphitization or thermal damage to the diamond. This invention significantly improves the polishing efficiency and service life of magnetic composite abrasives.
Smart Images

Figure CN120637077B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metallurgical technology, and more specifically, to a diamond-iron-based magnetic composite abrasive and its preparation method. Background Technology
[0002] Magnetorheological polishing (MRF) technology was first proposed by Kordonski in the 1990s. Unlike traditional surface finishing methods, MRF uses an external magnetic field to control the rheological changes of a magnetic polishing slurry, forming a flexible "micro-grinding head" with viscoelastic behavior. This head drives non-magnetic abrasive particles to perform shearing motion on the workpiece surface, thereby polishing the material. This characteristic enables MRF to achieve high material removal rates and high surface quality.
[0003] As a smart fluid, magnetorheological fluid exhibits the characteristics of a Newtonian fluid with low viscosity and high fluidity when no external magnetic field is present, but becomes a Bingham fluid with high viscosity and low fluidity when an external magnetic field is applied. Currently, magnetorheological fluids are mainly composed of three parts: a base fluid (including water, organic solvents, mineral oil, stabilizers, etc.), magnetic particles (such as carbonyl iron powder CIPs, Fe3O4, etc.), and abrasive particles (such as diamond powder, SiO2, CeO2, Al2O3, ZrO2, etc.). During magnetorheological polishing, magnetic particles align along magnetic lines of force under the influence of a magnetic field, forming magnetic chains of a certain strength. The abrasive particles are held in the gaps between these chains. The magnetic field controls the abrasive particles indirectly through the magnetic particles, but the control force and precision are insufficient. Furthermore, due to the relatively weak holding force of the magnetic chains on the abrasive particles, they easily slip out from the middle of the chains and escape from the polishing area during magnetorheological polishing, ultimately leading to a deterioration in polishing efficiency and effect. In summary, in existing magnetorheological fluid systems, magnetic particles and non-magnetic abrasives fail to form a cohesive whole, making it difficult to effectively control the magnitude of force, trajectory, and uniformity of distribution of non-magnetic abrasives using a magnetic field. This is a common challenge in magnetorheological polishing.
[0004] To address the aforementioned problems, an obvious solution is to combine magnetic particles and abrasive grains to form composite abrasives. Common methods include chemical methods, spray granulation, gas atomization, or high-temperature sintering. Among these, chemical methods have many limitations on the abrasive system. They can usually only coat the surface of magnetic particles with hydrolyzable or precipitable oxide abrasive grains such as SiO2, TiO2, and Al2O3. Moreover, the coating layer has low strength, thinness, and high cost, making it difficult to achieve practical applications. For example, Zhai et al. (Synthesis and characterization of nanocomposite Fe3O4 / SiO2 core-shellabrasives for high-efficiency ultrasound-assisted magneto-rheologicalpolishing of sapphire[J].CERAMICS INTERNATIONAL,2021,47(22):31681-31690.) used a chemical synthesis method to coat the surface of Fe3O4 magnetic particles with a SiO2 layer of about 20 nm thickness. Our team (Chinese Invention Patent, Application No.: 202410800284.6) prepared a diamond-iron-based spherical composite magnetic abrasive using iron-based magnetic powder and 1.0-1.5μm diamond abrasive grains as raw materials via spray granulation followed by reduction sintering. However, in this composite abrasive, most of the hard phase abrasive grains are distributed within the iron matrix, which not only reduces the magnetic saturation intensity of the composite abrasive but also, due to the weak grinding characteristics of magnetorheology, prevents the internal hard abrasive grains from being exposed during the magnetorheological process, thus hindering their grinding effect.
[0005] Both gas atomization and high-temperature sintering methods typically require high temperatures. For example, Zhang et al. (Preparation of white alumina spherical composite magnetic abrasive by gas atomization and rapid solidification[J].SCRIPTA MATERIALIA,2011,65(5):416-419.) prepared spherical composite abrasives using 7μm white corundum as abrasive grains and Fe-Si-Al-Ni soft magnetic alloy as the matrix, employing gas atomization at an atomization temperature of 1580℃. A. Anupam (Synthesis and Characterization of Sintered Magnetic Abrasive Particles having Alumina and Carbonyl Iron Powder[C]. IOP CONFERENCESERIES: MATERIALS SCIENCE&ENGINEERING, 2020, 804(1): 012002) obtained a magnetic composite abrasive of hydroxyl iron powder-alumina by high-energy ball milling of alumina abrasive particles and cold pressing, followed by high-temperature sintering and crushing of the compact at 1000-1545℃. Zhang Xinjian et al. (CN119709125A) mixed iron powder, nano iron powder and abrasive particles such as corundum or silicon carbide, and then sintered and crushed them at 800-1200℃ to obtain a core-shell structured magnetic abrasive. All three methods involve high-temperature processes, which can easily lead to the reaction of diamond with the iron matrix or graphitization. Therefore, diamond, the hardest material, is rarely used as abrasive particles. Hard ceramic abrasive particles such as alumina or silicon carbide are mostly used. This results in a lower lifespan and efficiency for composite abrasives. Furthermore, to improve the bonding force between the metal matrix and the hard abrasive grains, the aforementioned methods must use expensive nanoscale metal powders as raw materials. This significantly increases the production cost of composite abrasives.
[0006] In view of this, the present invention is proposed. Summary of the Invention
[0007] The purpose of this invention is to provide a diamond-iron-based magnetic composite abrasive and its preparation method, aiming to improve the hardness and service life of the abrasive particles in the composite abrasive.
[0008] This invention is implemented as follows:
[0009] In a first aspect, the present invention provides a method for preparing a diamond-iron-based magnetic composite abrasive, comprising:
[0010] Soft magnetic metal powder, iron oxide powder, metal oxide powder containing solid solution elements, and diamond abrasive grains are mixed evenly to obtain a mixed powder; wherein the particle size of the iron oxide powder, the metal oxide powder containing solid solution elements, and the diamond abrasive grains is smaller than the particle size of the soft magnetic metal powder; the solid solution elements contained in the metal oxide powder containing solid solution elements are selected from at least one of nickel, cobalt, and tin; the mass ratio of the total amount of iron oxide powder and the metal oxide powder containing solid solution elements to the mass of diamond abrasive grains is (5-10):1;
[0011] The mixed powder is cold-pressed to obtain a block-shaped green body;
[0012] The block green billet is subjected to high-temperature reduction to obtain a reduced billet. The high-temperature reduction process includes: holding at 400℃-450℃ in a hydrogen atmosphere for 0.2h-1.0h, then holding at 450℃-550℃ in a hydrogen atmosphere for 0.2h-1.0h, and then holding at 750℃-800℃ in a hydrogen atmosphere for 0.5h-1.5h.
[0013] In an optional embodiment, the metal oxide powder containing solid solution elements is nickel oxide powder, and the mass ratio of iron to nickel in the iron oxide powder and the metal oxide powder containing solid solution elements is (2.3-9.0):1.
[0014] In an optional embodiment, the total amount of iron oxide powder and metal oxide powder containing solid solution elements is in a mass ratio of (1.00-2.33):1 to the mass of soft magnetic metal powder.
[0015] In an optional embodiment, the soft magnetic metal powder is gas-atomized iron powder with a particle size of 38μm-150μm.
[0016] In an optional embodiment, the iron oxide powder and nickel oxide powder are ferric oxide powder and nickel oxide powder with a particle size ≤1μm;
[0017] And / or, the particle size of the diamond abrasive grains is 1μm-10μm.
[0018] Secondly, the present invention also provides a diamond-iron-based magnetic composite abrasive, which is prepared by the preparation method in any of the above embodiments.
[0019] In an optional embodiment, it includes a magnetic metal core and a magnetic metal-abrasive composite shell covering the surface of the magnetic metal core;
[0020] The magnetic metal-abrasive composite shell contains soft magnetic metal and diamond abrasive grains, with the soft magnetic metal being an iron-nickel alloy. The thickness of the magnetic metal-abrasive composite shell is 1-20 μm, with the mass fraction of iron being 50%-90%, nickel 1%-30%, and diamond 1%-40%.
[0021] In an optional implementation, commercially available ferric oxide and nickel oxide powders are used as raw materials. These materials are not only inexpensive and readily available, but also have fine particle sizes (≤1μm, typically 300-500nm). This powder can be rapidly reduced at low temperatures (400-550℃), achieving a reduction degree of over 90%, thereby reducing the damage to diamond abrasive grains caused by oxygen while maintaining high sintering activity. Furthermore, the elemental nickel generated from the nickel oxide powder can not only further alloy with iron, increasing the strength, hardness, and bonding force of the shell to the diamond abrasive grains, but also further inhibit the iron's promoting effect on the high-temperature graphitization of diamond and improve the corrosion resistance of the shell. To improve magnetorheological polishing efficiency, corrosive solvents such as hydrogen peroxide, acids, and alkalis are typically added to the magnetorheological fluid. Improving the corrosion resistance of the shell with nickel can further extend the service life of the composite abrasive.
[0022] It should be noted that diamond is highly susceptible to graphitization under conditions of oxygen, high temperature, and iron-based catalysts, losing its function as a hard abrasive. Therefore, when preparing magnetic composite abrasives using high-temperature sintering methods, iron and nickel oxides are generally not used as the bonding material for the shell; instead, elemental iron powder or its alloy powders are used. This results in excessively high bonding temperatures. Some studies have had to use expensive nano-iron powders to lower the bonding temperature. Even so, to achieve effective bonding of the shell metal to the hard abrasive grains, the final sintering temperature is usually above 1000℃. Because diamond undergoes significant graphitization above 900℃, there are few reports on diamond-iron-based composite abrasives. However, as the hardest natural substance, diamond has a significant performance advantage in terms of service life compared to other abrasives (such as corundum, silicon carbide, and other ceramic abrasives).
[0023] This invention offers the following advantages: It utilizes readily available and inexpensive iron oxide powder, nickel oxide powder, and diamond abrasive grains as the shell material. Employing a low-temperature pre-reduction + high-temperature reduction sintering process, over 90% of the iron oxide powder and metal oxide powder containing solid solution elements (such as nickel oxide) are first reduced at low temperatures, minimizing oxygen damage to the diamond under high-temperature conditions while maintaining the powder's sintering activity. Then, sintering at a maximum temperature of 800℃ allows the iron and nickel to alloy and densify, improving the shell's strength, hardness, corrosion resistance, and effective bonding with the diamond abrasive grains, while preventing significant graphitization or thermal damage to the diamond. This invention significantly improves the polishing efficiency and service life of magnetic composite abrasives. Attached Figure Description
[0024] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0025] Figure 1 SEM image of the magnetic composite abrasive with a core-shell structure prepared in Example 1;
[0026] Figure 2 This is a schematic diagram of the core-shell structured magnetic composite abrasive prepared in Example 1.
[0027] Figure 3 This is an elemental surface distribution diagram of a magnetic composite abrasive with a core-shell structure. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0029] Existing core-shell magnetic abrasives generally cannot use diamond as the hard phase, but can only use hard phases with lower hardness and shorter lifespan, such as silicon carbide, which significantly affects product performance. This invention creatively utilizes iron oxide and nickel oxide, materials not commonly used in the art, as the solid phase raw materials for the shell layer. This results in higher sintering activity, allowing solidification below 800℃. Through optimized high-temperature reduction processes, a high-strength, high-hardness, and highly corrosion-resistant Fe-Ni matrix can be formed, while simultaneously preventing the diamond in the shell layer from graphitizing.
[0030] This invention provides a method for preparing a diamond-iron-based magnetic composite abrasive, comprising:
[0031] S1. Preparation of mixed powder
[0032] A mixed powder is prepared by uniformly mixing soft magnetic metal powder, iron oxide powder, metal oxide powder containing a solid solution element, and diamond. The particle sizes of the iron oxide powder, the metal oxide powder containing the solid solution element, and the diamond are all smaller than the particle size of the soft magnetic metal powder to ensure a complete coating of large iron powder particles during subsequent pressing and molding. The solid solution element in the metal oxide powder containing the solid solution element is selected from at least one of nickel, cobalt, and tin, and can be any one or more of these elements.
[0033] Specifically, in this embodiment of the invention, the solid solution element refers to the element that forms a solid solution with the main element (iron). Nickel, cobalt, and tin can all form solid solutions. In addition to increasing strength and hardness, nickel can also improve corrosion resistance, which is beneficial to the improvement of product performance compared to other solid solution elements.
[0034] In some embodiments, the preparation process of the mixed powder includes: mixing soft magnetic metal powder, iron oxide powder, metal oxide powder containing solid solution elements, diamond, solvent, and binder, followed by drying to remove the solvent. The addition of solvent ensures uniform dispersion of the binder and uniform mixing of the raw materials; the binder can increase the bonding force between particles during cold pressing and is decomposed and removed during subsequent high-temperature reduction.
[0035] To better form a coating and a core-shell structure with a superior morphology, while simultaneously obtaining composite powder with the desired particle size, the particle size of each raw material was controlled: the soft magnetic metal powder can be gas-atomized iron powder or hydroxyl iron powder; for example, if it is gas-atomized iron powder, the particle size is 38μm-150μm; the iron oxide powder is ferric oxide powder with a particle size ≤1μm; the metal oxide powder containing solid solution elements is nickel oxide powder with a particle size ≤1μm; and the diamond abrasive grains have a particle size of 1μm-10μm. Specifically, the aforementioned gas-atomized iron powder is a commercially available raw material, a fine iron-based powder prepared through gas atomization technology, widely used in powder metallurgy, 3D printing, magnetic materials, welding materials, and other fields. The particle size of the composite abrasive is mainly related to the particle size of the raw material (gas-atomized iron powder), the cold pressing process, the heat treatment temperature, and the degree of crushing. This composite abrasive can be heat-treated later, which not only improves the bonding strength of the powder but also enhances the matrix's hold on the diamond abrasive grains. Therefore, magnetorheological fluids made with composite abrasives have advantages such as good magnetorheological effect, high polishing efficiency, short response time, high polishing precision, and long service life.
[0036] To obtain near-spherical particle products, the inventors optimized the dosage of the main raw materials: the mass ratio of iron to nickel in iron oxide powder and metal oxide powder containing solid solution elements is (2.3-9.0):1, such as 2.3:1, 3.0:1, 4.0:1, 5.0:1, 6.0:1, 7.0:1, 8.0:1, 9.0:1, etc.; preferably, the metal oxide powder containing solid solution elements is nickel oxide powder, and the mass ratio of iron to nickel in iron oxide powder and nickel oxide powder is 4:1. The mass ratio of the total amount of iron oxide powder and metal oxide powder containing solid solution elements to soft magnetic metal powder is (1.00-2.33):1, preferably 7:3. The mass ratio of the total amount of iron oxide powder and metal oxide powder containing solid solution elements to diamond is (5-10):1, such as 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc., preferably 10:1. It is advisable to control the amount of each raw material within the above range, which is beneficial to improve its hardness, corrosion resistance and holding force on diamond abrasive grains while maintaining the magnetic saturation strength of the magnetic metal shell.
[0037] In some embodiments, the adhesive may be a polyvinyl alcohol solution, but is not limited thereto. The solvent may be water, ethanol, acetone, etc. There are no limitations on the amount of adhesive and solvent used, and they can be used in combination over a wide range of applications.
[0038] In some embodiments, when drying after mixing, the drying method can be adopted, and the drying temperature can be controlled at 50℃-80℃, such as 50℃, 60℃, 70℃, 80℃, etc.; the drying time is 10h-15h, such as 10h, 11h, 12h, 13h, 14h, 15h, etc.
[0039] S2, Cold pressing
[0040] The mixed powder is cold-pressed to obtain a block green body.
[0041] In some embodiments, the dried mixed powder of S1 is placed in a mold and cold-pressed under a pressure of 10MPa-40MPa, specifically 10MPa, 15MPa, 20MPa, 25MPa, 30MPa, 35MPa, or 40MPa. To obtain a uniform pressing effect, the holding time is 1-3 minutes, such as 1 minute, 2 minutes, or 3 minutes.
[0042] It should be noted that a suitable mold is required during cold pressing to achieve better density after powder mixing. To avoid the influence of external environment and impurities on the mixed powder, such as impurities in the mold, cold pressing should be carried out in a clean mold at room temperature and pressure.
[0043] S3, High-temperature reduction
[0044] The blocky green blank obtained by S2 is subjected to high-temperature reduction to reduce the oxides and form a reduced blank of iron-iron alloy-diamond.
[0045] In some embodiments, to ensure sufficient reduction, the high-temperature reduction process can be divided into three stages: reacting at 400℃-450℃ for 0.2h-1.0h, then reacting at 450℃-550℃ for 0.2h-1.0h, and finally reacting at 750℃-800℃ for 0.5h-1.5h, with the total reaction time controlled to be 1h-3h. This embodiment of the invention employs a low-temperature pre-reduction + high-temperature reduction sintering process, enabling iron oxide and nickel oxide to serve as shell materials. With a maximum sintering temperature of 800℃, a high-strength, high-hardness, and highly corrosion-resistant Fe-Ni matrix can be formed, while simultaneously preventing the graphitization of diamond in the shell.
[0046] Specifically, the temperature of the first-stage high-temperature reduction can be 400℃, 430℃, 450℃, etc., and the reaction time can be 0.2h, 0.5h, 0.8h, 1.0h, etc.; the temperature of the second-stage high-temperature reduction can be 450℃, 480℃, 500℃, 530℃, 550℃, etc., and the reaction time can be 0.2h, 0.5h, 0.8h, 1.0h, etc.; the temperature of the first-stage high-temperature reduction can be 750℃, 780℃, 800℃, etc., and the reaction time can be 0.5h, 1.0h, 1.5h, etc.
[0047] In some embodiments, the reduction atmosphere can be a hydrogen atmosphere, but is not limited thereto. To avoid the influence of the external environment on the reduction process, such as oxygen in the air, high-temperature reduction can be carried out in hydrogen with a purity of 99.99% at a gas flow rate of 2 L / min.
[0048] Taking nickel as an example to illustrate the reaction principle, during the high-temperature reduction process, Ni2O3 is reduced to Ni, Fe2O3 is first reduced to Fe3O4 and then to FeO, and finally to Fe. At the same time, at a high temperature of 800℃, Ni and Fe diffuse to form an Fe-Ni alloy.
[0049] S4. Crushing and screening
[0050] A core-shell structured magnetic composite abrasive is obtained by crushing and sieving the reduced billet.
[0051] Specifically, the block-shaped green blank is first placed in a crusher and crushed into powder, then passed through a 200-300 mesh sieve to finally obtain a core-shell structured magnetic composite abrasive.
[0052] It should be noted that the preparation of composite abrasives with spherical structures by mixing, stirring, drying, cold pressing, high-temperature reduction, and crushing and sieving is not only simple and inexpensive, but also allows for better control of particle size (e.g., 75-105 μm). This results in magnetorheological fluids made from this composite powder having both good magnetic response and good magnetorheological effect and polishing performance.
[0053] This invention also provides a diamond-iron-based magnetic composite abrasive, which is prepared by the preparation method in any of the above embodiments. The prepared diamond-iron-based magnetic composite abrasive has the advantages of high strength and hardness, corrosion resistance, and long service life.
[0054] In some embodiments, it includes a magnetic metal core and a magnetic metal-diamond abrasive composite shell covering the surface of the magnetic metal core; wherein the magnetic metal-diamond abrasive composite shell contains soft magnetic metal and diamond abrasive particles, and the soft magnetic metal is an iron-nickel alloy.
[0055] Furthermore, the thickness of the magnetic metal-diamond abrasive composite shell is 1-20 μm (e.g., 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, etc.), wherein the mass fraction of iron is 50%-90% (e.g., 50%, 60%, 70%, 80%, 90%, etc.), the mass fraction of nickel is 1%-30% (e.g., 1%, 5%, 10%, 15%, 20%, 25%, 30%, etc.), and the mass fraction of diamond abrasive is 1%-40% (e.g., 1%, 5%, 10%, 20%, 30%, 40%, etc.). If the nickel content is too low, the shell's holding power for the diamond abrasive or its corrosion and wear resistance will decrease; if the iron content is too low, it will reduce the magnetism of the core-shell structure magnetic abrasive; and if the reduction temperature is too low, the Fe-Ni alloy layer cannot be formed on the surface, resulting in a lower bonding strength between the shell and the abrasive.
[0056] In a preferred embodiment, the magnetic metal-diamond abrasive composite shell is composed of an iron-nickel alloy and diamond abrasive grains, wherein the mass fraction of iron is 80%, the mass fraction of nickel is 20%, and the mass fraction of diamond abrasive grains is 10%. The mass fractions of iron, alloying elements, and diamond abrasive grains are preferably within the above-mentioned range. Within this range, the iron content and diamond abrasive grain content can be adjusted as needed to meet different process requirements.
[0057] It should be noted that while properly controlling the proportion of diamond abrasive grains can effectively improve polishing efficiency, an excessively high proportion of diamond abrasive grains will reduce the volume fraction of the metal matrix, thereby decreasing the specific saturation magnetic intensity of the composite abrasive, leading to a longer response time and weaker grinding force. Simultaneously, too many diamond abrasive grains can result in insufficient holding force of the matrix around the diamond, making it easier for diamond particles to detach. The size of the diamond abrasive grains affects both polishing efficiency and polishing quality. Increasing the diamond abrasive grain size, while improving polishing efficiency, will correspondingly reduce polishing quality.
[0058] This invention also provides a magnetic composite abrasive, including the diamond-iron-based magnetic composite abrasive described in any of the above embodiments. Specifically, since the diamond-iron-based magnetic composite abrasive provided by this invention is a solid powder with high bonding strength, controllable particle size, and high particle size concentration, it can impart good magnetorheological properties to the magnetorheological fluid and can be used for magnetorheological polishing.
[0059] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0060] Example 1
[0061] This embodiment provides a method for preparing diamond-iron-based magnetic composite abrasive, the steps of which are as follows:
[0062] (1) Preparation of mixed powder
[0063] Mixing: 30g of gas-atomized iron powder, 56.18g of Fe2O3 powder, 13.82g of Ni2O3 powder, and 7g of diamond powder were mixed in a mixer (at room temperature and pressure) for 2 hours. The mixed raw materials contained 64.76wt% Fe and 9.16wt% Ni. The particle size of the gas-atomized iron powder was 50-75μm, the particle size of the Fe2O3 powder was <1μm, the particle size of the Ni2O3 powder was 10μm, and the particle size of the diamond powder was 7μm.
[0064] Stirring: Add 35g of anhydrous ethanol and 5g of PVA solution (30% polyvinyl alcohol, 70% deionized water) to the mixed powder and stir in air for half an hour.
[0065] Drying: Place the stirred powder into a drying oven and dry it at 80°C for 12 hours to obtain mixed powder, and then vacuum seal it.
[0066] In the raw materials used in this embodiment, the mass ratio of iron to nickel in the total amount of iron oxide and nickel oxide is 4:1; the mass ratio of the total amount of iron oxide and nickel oxide to iron powder is 2.33:1; and the mass ratio of the total amount of iron oxide and nickel oxide to diamond abrasive is 10:1.
[0067] (2) Cold pressing
[0068] Prepare the mold: Place the obtained mixed powder into a clean mold (the mold is circular, with a radius of 7.5cm and a height of 10cm respectively) and spread it evenly and compact it.
[0069] Cold pressing: Place the mold containing the mixed powder into the center of the hydraulic press platform, set the pressure parameters, and press into shape. Control the operating pressure to 20MPa and the pressing time to 2min.
[0070] (3) High-temperature reduction
[0071] The green blocks are placed in a vacuum furnace and evacuated to a vacuum level of 1×10⁻⁶. -1 The pressure was set below 1 Pa, and then hydrogen gas (99.99% purity) was introduced at a flow rate of 2 L / min. The temperature was maintained at 400℃ for 0.5 h, at 500℃ for 0.5 h, and at 800℃ for 1 h, for a total holding time of 2 h.
[0072] (4) Crushing and screening
[0073] The reduced block green material is placed into a crusher and thoroughly crushed. The crushed powder is then passed through a 100-200 mesh sieve to obtain diamond-iron-based magnetic composite abrasive.
[0074] Example 2
[0075] The only difference from Example 1 is the amount of raw materials used in step (1). The specific raw materials are as follows:
[0076] Mixing: Mix 40g of gas-atomized iron powder, 48.1g of Fe2O3 powder, 11.9g of Ni2O3 powder, and 6g of diamond (Dia) powder in a mixer for 2 hours. The particle size of the gas-atomized iron powder is 50-75μm, the particle size of the Fe2O3 powder is <1μm, the particle size of the Ni2O3 powder is 10μm, and the particle size of the Dia is 7μm.
[0077] In this embodiment: the mass ratio of iron to nickel in the total amount of iron oxide and nickel oxide is 4:1; the mass ratio of the total amount of iron oxide and nickel oxide to iron powder is 1.5:1; and the mass ratio of the total amount of iron oxide and nickel oxide to diamond abrasive grains is 10:1. The mixed raw materials contain 69.4 wt% Fe and 7.92 wt% Ni.
[0078] Example 3
[0079] The only difference from Example 1 is the amount of raw materials used in step (1). The specific raw materials are as follows:
[0080] Mixing: Mix 50g of gas-atomized iron powder, 40.1g of Fe2O3 powder, 9.9g of Ni2O3 powder, and 5g of diamond powder in a mixer for 2 hours. The particle size of the gas-atomized iron powder is 50-75μm, the particle size of the Fe2O3 powder is <1μm, the particle size of the Ni2O3 powder is 10μm, and the particle size of the diamond powder is 7μm.
[0081] In this embodiment: the mass ratio of iron to nickel in the total amount of iron oxide and nickel oxide is 4:1; the mass ratio of the total amount of iron oxide and nickel oxide to iron powder is 1:1; and the mass ratio of the total amount of iron oxide and nickel oxide to diamond abrasive grains is 10:1. The mixed raw materials contain 74.33 wt% Fe and 6.67 wt% Ni.
[0082] Example 4
[0083] The only difference from Example 1 is that the amount of raw materials used in step (1) is different. The mass of diamond powder is 14g, and the amount of other raw materials is the same as in Example 1.
[0084] In this embodiment: the mass ratio of iron to nickel in the total amount of iron oxide and nickel oxide is 4:1 (same as in Example 1); the mass ratio of the total amount of iron oxide and nickel oxide to iron powder is 2.33:1 (same as in Example 1); the mass ratio of the total amount of iron oxide and nickel oxide to diamond abrasive grains is 5:1. The mixed raw materials contain 60.78 wt% Fe and 8.60 wt% Ni.
[0085] Example 5
[0086] The only difference from Example 1 is that the amount of raw materials used in step (1) is different. The mass of iron oxide powder is 63.05g, the mass of nickel trioxide is 6.95g, and the amount of other raw materials is the same as in Example 1.
[0087] In this embodiment: the mass ratio of iron to nickel in the total amount of iron oxide and nickel oxide is 9:1; the mass ratio of the total amount of iron oxide and nickel oxide to iron powder is 2.33:1; and the mass ratio of the total amount of iron oxide and nickel oxide to diamond abrasive grains is 10:1. The mixed raw materials contain 69.25 wt% Fe and 4.61 wt% Ni.
[0088] Example 6
[0089] The only difference from Example 1 is that the amount of raw materials used in step (1) is different. The mass of iron oxide powder is 52.68g, the mass of nickel trioxide is 17.32g, and the amount of other raw materials is the same as in Example 1.
[0090] In this embodiment: the mass ratio of iron to nickel in the total amount of iron oxide and nickel oxide is 3:1; the mass ratio of the total amount of iron oxide and nickel oxide to iron powder is 2.33:1; and the mass ratio of the total amount of iron oxide and nickel oxide to diamond abrasive grains is 10:1. The mixed raw materials contain 62.47 wt% Fe and 11.49 wt% Ni.
[0091] Comparative Example 1
[0092] The only difference from Example 1 is that nickel oxide is not added, but replaced with an equal amount of iron oxide.
[0093] Comparative Example 2
[0094] The powder in this comparative example 1 was simply mechanically mixed and then used for magnetorheological polishing.
[0095] Comparative Example 3
[0096] The only difference from Example 1 is that the diamond abrasive grains in step (1) are replaced with alumina abrasive grains of the same size.
[0097] Comparative Example 4
[0098] The only difference from Example 1 was that the operating temperature was controlled at 850°C during the high-temperature reduction process, and the total holding time was 2 hours. Raman spectroscopy analysis showed that the graphitization rate of the diamond exceeded 7%, and no subsequent polishing test was performed.
[0099] Comparative Example 5
[0100] The only difference from Example 1 is that the amount of raw materials used in step (1) is different. The mass of diamond powder is 21g, and the amount of other raw materials is the same as in Example 1.
[0101] In this comparative example: the mass ratio of iron to nickel in the total amount of iron oxide and nickel oxide is 4:1 (same as in Example 1); the mass ratio of the total amount of iron oxide and nickel oxide to iron powder is 2.33:1 (same as in Example 1); the mass ratio of the total amount of iron oxide and nickel oxide to diamond abrasive grains is 3.33:1. The mixed raw materials contain 57.27 wt% Fe and 8.11 wt% Ni.
[0102] Experimental Example 1: The composite powder prepared in Example 1 was observed using a scanning electron microscope. Figure 1 As shown in the scanning electron microscope image, multiple tiny diamond abrasive grains are embedded on the surface of the iron-based particles.
[0103] like Figure 2 The image shown is a cross-sectional view of the composite powder prepared in Example 1, which has a core-shell structure.
[0104] The composition of the obtained core-shell structured iron-based diamond composite abrasive was analyzed by EDS, such as... Figure 3 As shown, this verifies the fact that diamond particles are embedded in the surface of spherical particles, and that Fe and Ni elements are evenly distributed in the composite abrasive.
[0105] The magnetic properties of the core-shell structured iron-based diamond composite abrasive were characterized multiple times using a vibrating sample magnetometer. The magnetic strength of the samples ranged from 140.8 to 176.1 emu / g, but all remained above 140 emu / g.
[0106] Experimental Example 2
[0107] The test examples and comparative examples provided composite abrasives for magnetorheological polishing of single-crystal silicon wafers, and the polishing results are shown in Table 1.
[0108] Test method: The roughness of the single crystal silicon workpiece before and after polishing was measured using a Mitutoyo SJ-210 handheld roughness tester from Japan.
[0109] Table 1 compares the magnetorheological processing effects of the composite abrasives provided in the embodiments and comparative examples.
[0110]
[0111]
[0112] As can be seen from Table 1, Example 1 showed the best polishing effect. Comparative Example 3, however, indicates that when alumina is used as the hard abrasive, the polishing efficiency is low, and the composite abrasive easily loses its polishing ability.
[0113] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a diamond-iron-based magnetic composite abrasive, characterized in that, include: Soft magnetic metal powder, iron oxide powder, metal oxide powder containing a solid solution element, and diamond abrasive grains are mixed evenly to obtain a mixed powder; wherein the particle size of the iron oxide powder, the metal oxide powder containing a solid solution element, and the diamond abrasive grains are all smaller than the particle size of the soft magnetic metal powder; the solid solution element contained in the metal oxide powder containing a solid solution element is nickel; the mass ratio of the total amount of the iron oxide powder and the metal oxide powder containing a solid solution element to the mass of the diamond abrasive grains is (5-10):1; The mixed powder is cold-pressed to obtain a block green body; The block green billet is subjected to high-temperature reduction to obtain a reduced billet; the high-temperature reduction process includes: holding at 400℃-450℃ in a hydrogen atmosphere for 0.2 h-1.0 h, then holding at 450℃-550℃ in a hydrogen atmosphere for 0.2 h-1.0 h, and then holding at 750℃-800℃ in a hydrogen atmosphere for 0.5 h-1.5 h. The soft magnetic metal powder is gas-atomized iron powder with a particle size of 38 μm-150 μm; The iron oxide powder is ferric oxide powder with a particle size ≤1 μm; The metal oxide powder containing solid solution elements is nickel oxide powder with a particle size ≤1 μm; The diamond abrasive grains have a particle size of 1 μm-10 μm.
2. The preparation method according to claim 1, characterized in that, The mass ratio of iron to nickel in the iron oxide powder and the metal oxide powder containing solid solution elements is (2.3-9.0):
1.
3. The preparation method according to claim 1, characterized in that, The total amount of the iron oxide powder and the metal oxide powder containing solid solution elements is in the mass ratio of the soft magnetic metal powder to (1.00-2.33):
1.
4. The preparation method according to claim 1, characterized in that, Also includes: The reduced billet is crushed, sieved, and vacuum-packed.
5. A diamond-iron-based magnetic composite abrasive, characterized in that, It is prepared by the preparation method according to any one of claims 1-4.
6. The diamond-iron-based magnetic composite abrasive according to claim 5, characterized in that, It includes a soft magnetic metal and a magnetic metal-abrasive composite shell coating the surface of the soft magnetic metal; The magnetic metal-abrasive composite shell contains soft magnetic metal and diamond abrasive grains, wherein the soft magnetic metal is an iron-nickel alloy.
7. The diamond-iron-based magnetic composite abrasive according to claim 6, characterized in that, The thickness of the magnetic metal-abrasive composite shell is 1-20 μm, wherein the mass fraction of iron is 50%-90%, the mass fraction of nickel is 1%-30%, and the mass fraction of diamond is 1%-40%.
Citation Information
Patent Citations
Magnetic abrasive material with core-shell structure and preparation method of magnetic abrasive material
CN119709125A
Multi-micro-cutting-edge diamond-iron-based spherical composite magnetic grinding material and preparation method and application thereof
CN118725824A
A self-sharpening polishing device with magnetorheological flexible polishing pad formed by dynamic magnetic field and polishing method thereof
US20180021910A1